Foundations of computer science - Forouzan, Behrouz A. (Thomson, 2008)
Based on the ACM model curriculum guidelines, this easy-to-read and easy-to-navigate text covers all the fundamentals of computer science required for first year students embarking on a computing degree. Divided into five parts - computer and data, computer hardware, computer software, data organization and with an introduction to some of the more advanced topics - Foundations of Computer Science gives students a bird's eye view of the subject. Each chapter includes key terms, summaries, review questions, multiple-choice questions, and exercises to enhance learning, while introducing tools such as UML, structure chart and pseudocode, which students will need in order to succeed in later courses. The text is also supported by numerous figures, examples, exercises, selected solutions and a test bank, all designed to ease and aid the learning process.